Environmental and anthropogenic factors associated with the likelihood of detecting Salmonella in agricultural watersheds. (1st August 2022) - Toro, Magaly; Weller, Daniel; Ramos, Romina; Diaz, Leonela; Alvarez, Francisca P.; Reyes-Jara, Angelica; Moreno-Switt, Andrea I.; Meng, Jianghong; Adell, Aiko D.
Abstract: Surface water is one of the primary sources of irrigation water for produce production; therefore, its contamination by foodborne pathogens, such as Salmonella, may substantially impact public health. In this study, we determined the presence of Salmonella in surface water and characterized the relationship between Salmonella detection and environmental and anthropogenic factors. From April 2019 to February 2020, 120 samples from 30 sites were collected monthly in four watersheds located in two different central Chile agricultural regions (N = 1080). Water samples from rivers, canals, streams, and ponds linked to each watershed were obtained. Surface water (10 L) was filtrated in situ, and samples were analyzed for the presence of Salmonella . Salmonella was detected every month in all watersheds, with a mean detection percentage of 28% (0%–90%) across sampling sites, regardless of the season. Overall, similar detection percentages were observed for both regions: 29.1% for Metropolitan and 27.0% for Maule. Salmonella was most often detected in summer (39.8% of all summer samples tested positive) and least often in winter (14.4% of winter samples). Random forest analysis showed that season, water source, and month, followed by latitude and river, were the most influential factors associated with Salmonella detection. The influences of water pH and temperature (categorized as environmental factors) and factors associated with human activity (categorized as anthropogenic factors) registered at the sampling site were weakly or not associated with Salmonella detection. In conclusion, Salmonella was detected in surface water potentially used for irrigation, and its presence was linked to season and water source factors. Interventions are necessary to prevent contamination of produce, such as water treatment before irrigation. Graphical abstract: Image 1 Highlights: Salmonella was detected in all watersheds, including sources used for irrigation. Salmonella isolation showed a higher likelihood of water contamination in summer. Likelihood of Salmonella detection varied between watersheds and water types. The highest-ranked anthropogenic factor associated with Salmonella is crop presence.